The Influence of Work Motivation and Work Discipline on Employee Performance at PT Tunas Mekar Farm, Bogor Regency - Pupu Pahrudin; Veta Lidya Delimah Pasaribu (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to determine the effect of employee work motivation and work discipline simultaneously on employee performance at PT Tunas Mekar Farm, Bogor Regency. The research approach used in this research is the Quantitative Method. The sampling technique consisted of 76 people. The data collection technique in this research uses a questionnaire distributed to employee. Data analysis techniques Data using Descriptive Analysis, Validity Test, Reliability, Simple, Multiple Regression Analysis, Classical Assumption Test, t Test (Partial), F Test (Simultaneous), Correlation Coefficient and Determination. The results of this research are that Service Quality has a significant effect on Consumer Loyalty with the regression equation Y = 4.893+0.504X1+0.209X2 + e, the correlation coefficient value is 0.793, which means the level of relationship between the dependent variable and the independent variable is strong with a coefficient of determination of 62.9% and the results of the t test show that the Work Motivation variable has a calculated t of 3.704 > t table of 1.665 (sig. α=0.05 and df = n-k, namely 73) with a significance level of 0.000 which is smaller than 0.05, then Ha is accepted . This means that Work Motivation has a positive effect on Employee Performance and the Work Discipline variable has a calculated t of 3.926 > t table of 1.665 (sig. α=0.05 and df = n-k, namely 73) with a significance level of 0.000 which is smaller than 0, 05, then Ha is accepted. This means that work discipline has a positive effect on employee performance.